Pelatihan Strategi Manajemen Sumberdaya dalam Mengelola Bisnis bagi UKM Goyang 1.1 Kabupaten Kubu Raya - Syamsuri Syamsuri; Nuraini Asriati; Junaidi H. Matsum; Achmadi Achmadi; Witarsa Witarsa; M. Basri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to increase entrepreneurial competency through resource management training in business management. The partner in this activity was the Rengginang Goyang 1 UKM, Kubu Raya Regency. The method of implementing this service was community education-based training. This activity was evaluated by comparing the results of the pretest with the posttest and analyzed descriptively. The results of the dedication showed that there had been an increase in participants' knowledge regarding resource management strategies in managing the business. It was shown from the pretest and posttest values; the pretest value was 35%, and at the time of the posttest, it increased to 65%. In addition to the test results, the observation showed that the participants were very satisfied with this activity.